1988
DOI: 10.1111/j.1755-3768.1988.tb08532.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal sensation in acute angle closure glaucoma

Abstract: Corneal sensation was found to be decreased in eyes affected by acute angle closure glaucoma. In those patients with a short history (less than four days) the difference in sensation between the two eyes was only detectable using the Cochet-Bonnet aesthesiometer and not by using cotton wool. Patients with a longer history had a more marked decrease in corneal sensation that was detectable by both methods. Corneal sensation in both groups tended to recover partially on normalization of the intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Similar findings were reported in prior studies involving human PCG patients . Prior studies in human patients have shown that buphthalmos at an early age may be associated with significant reduction in corneal sensitivity, although in these patients, increased CD is also associated with increased CT and corneal edema . In 1988, Patel and others noted that persistent corneal edema led to decreased corneal sensitivity, even after normalization of IOP, in patients that had prolonged elevation of IOP .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar findings were reported in prior studies involving human PCG patients . Prior studies in human patients have shown that buphthalmos at an early age may be associated with significant reduction in corneal sensitivity, although in these patients, increased CD is also associated with increased CT and corneal edema . In 1988, Patel and others noted that persistent corneal edema led to decreased corneal sensitivity, even after normalization of IOP, in patients that had prolonged elevation of IOP .…”
Section: Discussionsupporting
confidence: 80%
“…Prior studies in human patients have shown that buphthalmos at an early age may be associated with significant reduction in corneal sensitivity, although in these patients, increased CD is also associated with increased CT and corneal edema . In 1988, Patel and others noted that persistent corneal edema led to decreased corneal sensitivity, even after normalization of IOP, in patients that had prolonged elevation of IOP . In the veterinary literature, one prospective clinical study evaluating canine eyes with buphthalmos and/or chronically elevated intraocular pressure prior to evisceration with intraocular prosthesis placement determined that corneal sensitivity in these eyes was significantly reduced relative to contralateral control eyes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diurnal fluctuations in corneal sensitivity also occur 24 . Numerous pathologic conditions of the eye have been shown to increase the corneal touch threshold in humans including scleritis, 25 keratoconjunctivitis sicca, 26 herpes viral keratitis, 27 corneal edema, 28,29 and glaucoma 30,31 . Additionally, systemic diseases that can affect the peripheral nerves, such as diabetes mellitus, myasthenia gravis, and leprosy, can also lead to an increase in corneal touch threshold 14,32–36 …”
Section: Discussionmentioning
confidence: 99%
“…In a study of five human patients with prolonged rise in IOP, no patients reverted to normal corneal sensitivity even after normalization of IOP 30 . Those authors proposed a lasting damage to corneal nerves due to corneal edema 30 . Corneal edema has been shown to decrease corneal sensitivity in humans 28,29 .…”
Section: Discussionmentioning
confidence: 99%